A New Static PV Array Reconfiguration for Increasing Maximum Power, Case Study: Al-Nahrain University - Mahmood, Anas (Iraqi Journal for Electrical and Electronic Engineering, 2025)
Enhancing the generated power. Different conventional reconfiguration techniques can be used for this purpose like totalcross-tied (TCT), bridge-linked (BL), and series-parallel (SP) . . . etc. This article propose a new static reconfigurationtechnique named Row Odd Even reconfiguration (ROE) to increase the maximum power generated from PV array withthe effect of partial shading condition. The proposed reconfiguration has been tested on a 3×22 PV array suggested toprovide power to the department of electronic and communications engineering at Al-Nahrain University, Baghdad,Iraq. The results of the proposed reconfiguration are compared with the (SP, TCT, and Zig-zag) in terms of mismatchpower losses (MPL), fill factor (FF), and efficiency (η) at the maximum generated power of PV array. In all cases, theperformance of the new reconfiguration gave the best performance when compared with (SP, TCT, and Zig-zag). Thenew reconfiguration achieved an improvement in the maximum power point (MPP) and efficiency about 33%, 28% and7% when compared with the (SP), (TCT) and (Zig-zag) reconfigurations respectively.